A general framework for semantics-based bottom-up abstract interpretation of logic programs - Barbuti, Roberto; Giacobazzi, Roberto; Levi, Giorgio 1942- (1991)
Abstract: "The theory of abstract interpretation provides a formal framework to develop advanced dataflow analysis tools. The idea is to define a non-standard semantics which is able to compute, in finite time, an approximated model of the program. In this paper we define an abstract interpretation framework based on a fixpoint approach to the semantics. This leads to the definition, by means of a suitable set of operators, of an abstract fixpoint characterization of a [pi]-model associated with the program. Thus, we obtain a specializable abstract framework for bottom-up abstract interpretations of definite logic programs. The specialization of the framework is shown on two examples, namely ground dependences analysis and depth-k analysis."
Keywords: Logic programming